An Approach to Benzophosphole Oxides through Silver‐ or Manganese‐Mediated Dehydrogenative Annulation Involving CC and CP Bond Formation1. Issue 49 (11th October 2013) - Unoh, Yuto; Hirano, Koji; Satoh, Tetsuya; Miura, Masahiro
<x xml:space="preserve">Abstract</x> Benzophosphole construction was achieved through the AgI‐mediated dehydrogenative annulation of phenylphosphine oxides with internal alkynes in a process involving CC and CP bond formation. A wide range of asymmetrical phenylacetylenes could be employed and the reactions proceeded with perfect regioselectivity. Moreover, the annulation could be conducted even at room temperature when a MnIII promoter was used in place of AgI.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>